Steroids and anthraquinones from the deep-sea-derived fungus Aspergillus nidulans MCCC 3A00050. (April 2019) - Xing, Cui-Ping; Wu, Jia; Xia, Jin-Mei; Fan, Shao-Qiang; Yang, Xian-Wen
Abstract: Aspergillus nidulans MCCC 3A00050 was isolated from a deep-sea sediment sample of the western Pacific Ocean. A systematic investigation on its chemical constituents led to the isolation of 19 compounds, including 13 steroids (1 –13 ), four anthraquinones (14 –17 ), one phenolics (18 ), and one chromanone (19 ). For the first time, three diosgenins (1 –3 ) were isolated from fungi, three ergosterols (4 –6 ) from the genus of Aspergillus, while other 11 miscellaneous compounds (7 –11 and14 –19 ) from the species of Aspergillus nidulans . The isolation of diosgenins (1 –3 ) and ergosterols (4 –6 ) might be used as chemotaxonomic markers for the genus of Aspergillus and the species of Aspergillus nidulans, respectively. Graphical abstract: Thirteen steroids (1 –13 ), four anthraquinones (14 –17 ), one phenolics (18 ), and one chromanone (19 ) were isolated from the deep-sea-derived fungus Aspergillus nidulans MCCC 3A00050. Three diosgenins (1 –3 ) might be used as chemotaxonomic markers for the genus of Aspergillus, while ergosterols (4 –6 ) might be taken as indicative compounds to distinguish A. nidulans from the other Aspergillus species.Image 1 Highlights: Isolation of 19 miscellaneous compounds. Structure elucidation achieved mainly by analysis of NMR and MS data. Diosgenins (1 –3 ) are of chemotaxonomic significance for Aspergillus species. Ergosterols (4 –6 ) are indicative compounds for Aspergillus nidulans.